THE EFFECTIVENESS OF THE APPLICATION OF THE PBL MODEL IN IPS SUBJECTS ON COOPERATION IN CLASS III HANG TUAH 10 JUANDA ELEMENTARY SCHOOL - Ananda Roqiba Faradisi; Danang Prastyo (Media Inovasi Pendidikan dan Publikasi, 2024)
The purpose of the written research is so that researchers can find out about teachers' performance in implementing the PBL (Problem Based Learning) learning model in social studies subjects for class III collaboration at Hang Tuah 10 Juanda Elementary School. Researchers know the learning outcomes of students using the PBL learning model in social studies subjects in elementary schools. Researchers know and see students' responses when the PBL learning model is implemented in social studies subjects in elementary schools. Written research includes descriptive quantitative research. Written research with a Pre-Experimental Design research design with One Group Pretest-Posttest Design type. The population used was students at Hang Tuah 10 Juanda Elementary School with a sample of class III C students. The methods used were tests and questionnaires. According to research results processed using SPSS 23.0, it is known that the average n-gain value is 0.56 in the medium category. So it can be said that learning outcomes can be improved between the pretest and posttest scores. Thus, in the learning process using the PBL model, there is an increase in student learning outcomes in social studies subjects, cooperative material for class III elementary school. And it can be proven that the PBL application model is effectively used in social studies subjects with cooperative material.